Capacity of Higher Educational Institutions in Delivering Graduate Programs in Public Administration - Ederson de Los Trino Tapia (Indonesian Association for Public Administration, 2020)
The concern on capacity has become an intriguing study to examine the capacity of state universities and colleges (SUCs) and local universities and colleges (LUCs) in the Philippines to deliver quality graduate programs. This paper is a comparative assessment on the capacity of to deliver graduate programs in Public Administration of four HEIs in the National Capital Region (NCR), namely: Pamantasan ng Lungsod ng Maynila (PLM), Polytechnic University of the Philippines (PUP), University of the Philippines-National College of Public Administration (UP-NCPAG), and the University of Makati (UMak) using indicators in six capacity areas, to wit: Human Resources, Knowledge Management Resources, Physical/Material Resources, Organizational/Leadership Resources, Networking/Linkage Resources, and Cross-border Services employing a qualitative, multi-source case study research design such as direct observations, documents or archival records, verbal reports from key informants (key informant interviews or KII), survey questionnaire, and Focus Group Discussions (FGDs). The results show that UP-NCPAG is very strong in four capacity areas; PUP is strong in all capacity areas; UMak is very strong in two capacity areas, strong in two capacity areas, but moderate in two capacity areas; and PLM is very strong in one capacity area, strong in three areas, but moderate in two areas.